2004
DOI: 10.1210/me.2003-0133
|View full text |Cite
|
Sign up to set email alerts
|

Mitogenic Activity of Estrogens in Human Breast Cancer Cells Does Not Rely on Direct Induction of Mitogen-Activated Protein Kinase/Extracellularly Regulated Kinase or Phosphatidylinositol 3-Kinase

Abstract: We have addressed the question of rapid, nongenomic mechanisms that may be involved in the mitogenic action of estrogens in hormone-dependent breast cancer cells. In quiescent, estrogen-deprived MCF-7 cells, estradiol did not induce a rapid activation of either the MAPK/ERK or phosphatidylinositol-3 kinase (PI-3K)/Akt pathway, whereas the entry into the cell cycle was documented by the successive inductions of cyclin D1 expression, hyperphosphorylation of the retinoblastoma protein (Rb), activity of the promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
30
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 40 publications
7
30
0
Order By: Relevance
“…The nongenomic actions of estradiol include effects on calcium flux that occur rapidly without being mediated by transcriptional effects of nuclear ER (Nadal et al 2001, Song et al 2002, Gaben et al 2004. Based on the rapid activation of estrogen-induced MAPK phosphorylation including ERK, p38, and SAPK/JNK pathways, nongenomic effects should be involved in the signal activation in MCF-7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The nongenomic actions of estradiol include effects on calcium flux that occur rapidly without being mediated by transcriptional effects of nuclear ER (Nadal et al 2001, Song et al 2002, Gaben et al 2004. Based on the rapid activation of estrogen-induced MAPK phosphorylation including ERK, p38, and SAPK/JNK pathways, nongenomic effects should be involved in the signal activation in MCF-7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Hiscox et al (26) also showed that in tamoxifen-resistant epidermal growth factor receptor overexpressing MCF-7 cells, the combination of AZD0530 and the epidermal growth factor receptor inhibitor gefitinib blocked migration and invasion in an additive manner. A number of studies have shown that inhibiting c-Src activity in breast cancer cells blocks estrogen-induced cell cycle progression and mitogenesis (33,34). Additionally, c-Src inhibitors have also been shown to block estrogen-induced migration in endometrial cells (35) and disrupt adherans junctions in endothelial cells (36).…”
Section: Discussionmentioning
confidence: 99%
“…2A). This is not entirely surprising as other studies have suggested that E 2 can be mitogenic without detectable activation of ERK1/2 in MCF-7 cells (19,21).…”
Section: Discussionmentioning
confidence: 52%
“…For instance, Lewis et al have recently shown that PD98059 had no significant effect on E 2 -induced phosphorylation of activating transcription factor-2 (20). Other studies in which estrogendeprived cells were treated with E 2 reported no activation of the MEK/ERK pathway despite the stimulation of entry into cell cycle progression, and treatment of these cells with U0126 was only partially inhibitory on cell cycle progression (21). Similarly, Bonapace et al reported that treatment of MCF-7 cells with E 2 allowed the cells to overcome a G1 block induced by HMG-CoA reductase inhibitors and that this effect did not require activation of ERK1/2 (22).…”
Section: Introductionmentioning
confidence: 99%